Protein-mediated stabilization and nicking of the nontemplate DNA strand dramatically affect R-loop formation in vitro - Ethan Holleman; Thomas E. Catley; Tadas Sereiva; Stella R. Hartono; Alice L. B. Pyne; Frédéric Chédin (Proceedings of the National Academy of Sciences, 2025)
R-loops are an important class of non-B DNA structures that form co-transcriptionally. Using in vitro transcription and unbiased quantitative sequencing readouts, we show that the addition of single-strand DNA binding proteins co-transcriptionally can drive a 3- to 5-fold increase of R-loop frequency without significant changes to R-loop distribution. We propose that this is caused by stabilizing and preventing the collapse of short nascent R-loops. This suggests that R-loop formation is highly dynamic and highlights single strand binding proteins as players in cellular R-loop regulation. We further show that nontemplate strand DNA nicks are powerful initiators of R-loop formation, increasing R-loop frequencies by up to two orders of magnitude. Atomic force microscopy revealed that the nontemplate strand in nick-initiated structures is often flayed away from the RNA:DNA hybrid and engaged in self-pairing, creating unique forked R-loop features. DNA nicks, one of the most frequent DNA lesions in cells, are therefore potential hotspots for opportunistic R-loop initiation and may cause the formation of a distinct class of R-loops. Overall, this work highlights the importance of the displaced single-strand on R-loop initiation and dynamics.